Macroeconomics fluctuations and its impact on musharaka financing - Faizul Mubarok; Abdul Hamid; Mohammad Nur Rianto Al Arif (University of Merdeka Malang, 2020)
This study aims to analyze the effect of the movement of macroeconomic variables on financing using the musharaka contract on Islamic banks. This study consists of sharia commercial banks and sharia business units using monthly data from January 2004 to December 2019. This study uses Vector Error Correction Model (VECM) to answer the research objectives. All variables tested have an influence on financing using the musharaka contract. Financing using the musharaka contract responds negatively to movements in the exchange rate and interest rates while inflation responds positively and negatively. Islamic banking needs to prepare more reserve funds in the face of such movements before achieving stability. The musharaka contract financing itself dominates the forecasting then followed by interest rates, inflation, and exchange rates. Therefore, Islamic banking needs to prepare a reserve fund in the face of these shocks before achieving stability. JEL Classification: E31, E43, E52, G32 How to Cite:Mubarok, F., Hamid, A., Al Arif, M. N. R. (2020). Macroeconomics fluctuations and its impact on musharaka financing. Jurnal Keuangan dan Perbankan, 24(2), 164-174.DOI: https://doi.org/10.26905/jkdp.v24i2.4061